DEVELOPMENT OF THE ADMINISTRATION OF TAXATION OF MEDIUM-SIZED BUSINESS SERVICES IN UZBEKISTAN (Academicia Globe: Inderscience Research, 2023)
Uzbekistan recognizes that the medium-sized business service sector plays an important role in economic growth and modernization. This sector, which includes a variety of enterprises, has the potential for innovation, employment and economic diversification. At the same time, the effective management of taxation in this sector has attracted the attention of politicians and business leaders. This article includes extensive research on the development of tax administration mechanisms tailored to the specific needs of Uzbekistan's medium-sized business service sector. It examines the challenges facing historical tax systems, the reforms initiated to address them, and their impact on sector growth and competitiveness. This analysis highlights the importance of a balanced taxation system that encourages entrepreneurship, ensures compliance and encourages investment. By examining the dynamic landscape of tax administration, this study contributes to the ongoing debate about economic changes in Uzbekistan and the changing role of taxation in its growing medium-sized business service sector.